Expression and clinical significance of interleukin-6 pathway in cholangiocarcinoma - Gu, Dongqing; Zhao, Xin; Song, Jing; Xiao, Jianmei; Zhang, Leida; Deng, Guohong; Li, Dajiang (Frontiers in Immunology, 2024)
Background: Cholangiocarcinoma (CCA) is a typical inflammation-induced malignancy, and elevated serum interleukin-6 (IL-6) levels have been reported to be linked to the onset and progression of CCA. We aim to investigate the potential prognostic value of the IL-6 pathway for CCA.We detected the expressions of IL-6, IL-6R, glycoprotein (gp130), C-reactive protein (CRP), Janus kinase 2 (JAK2), and signal transducer and activator of transcription 3 (STAT3) in CCA tissue microarray using multiplex immunofluorescence. Furthermore, the clinical associations and prognostic values were assessed. Finally, single-cell transcriptome analysis was performed to evaluate the expression level of IL-6 pathway genes in CCA.The results revealed that the expression of IL-6 was lower, while the expression of STAT3 was higher in tumor tissues compared to normal tissues. Especially in tumor microenvironment, the expression of IL-6 pathway genes was generally downregulated. Importantly, gp130 was strongly correlated with JAK2 in tumor tissues, while it was moderately correlated with JAK2 in normal tissue. Although none of the gene expressions were directly associated with overall survival and disease-free survival, our study found that IL-6, IL-6R, CRP, gp130, and JAK2 were inversely correlated with vascular invasion, which is a risk factor for poor prognosis in patients with CCA.The findings from this study suggest that the IL-6 signaling pathway may have a potential prognostic value for CCA. Further investigation is needed to understand the underlying molecular mechanisms of the IL-6 pathway in CCA.